Small-pads resistive micromegas - Alviggi, Mariagrazia; Franchino, Silvia (Journal of Instrumentation, 2017)
Resistive micromegas is now a mature technology for High Energy Physics experiments. In the ATLAS experiment at CERN 128 multilayers large size ( 2 m 2 ) micromegas chambers will be employed in the upgrade of the Muon Spectrometer (2019/2020), and will operate at moderate hit rate up to about 15 kHz/cm 2 during the phase of High-Luminosity-LHC . Future upgrades and detectors at future accelerators will require operation at rates up to three orders of magnitude higher. In this paper we present the development of micromegas with a small-pads readout (few mm 2 in size) aiming at precision tracking in high rate environment without efficiency loss up to a few MHz/cm 2 . The detector layout and the construction technique will be reviewed, along with the first results obtained with radioactive sources. Outlooks on future developments will also be illustrated.